2013
DOI: 10.1186/1742-4755-10-30
|View full text |Cite
|
Sign up to set email alerts
|

The case for investing in family planning in the Pacific: costs and benefits of reducing unmet need for contraception in Vanuatu and the Solomon Islands

Abstract: BackgroundUnmet need for family planning in the Pacific is among the highest in the world. Better understanding of required investments and associated benefits of increased access to family planning in the Pacific may assist prioritisation and funding.MethodsWe modelled the costs and associated health, demographic and economic impacts of reducing unmet need for family planning between 2010–2025 in Vanuatu and the Solomon Islands. Baseline data were obtained from census reports, Demographic and Health Surveys, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 17 publications
3
24
1
Order By: Relevance
“…From the included studies, six articles assessed the cost effectiveness of improving family planning interventions in Mexico [25], India [26], Afghanistan [27], Nigeria [28], Uganda [29] and Pacific islands [30], of which four were evaluating family planning as one of several interventions to reduce maternal mortality [2528]. The remaining three studies assessed strategies to reduce the unmet meet of family planning for HIV-infected women by means of providing integrated family planning and HIV services in multiple countries in Africa [24,31,32].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…From the included studies, six articles assessed the cost effectiveness of improving family planning interventions in Mexico [25], India [26], Afghanistan [27], Nigeria [28], Uganda [29] and Pacific islands [30], of which four were evaluating family planning as one of several interventions to reduce maternal mortality [2528]. The remaining three studies assessed strategies to reduce the unmet meet of family planning for HIV-infected women by means of providing integrated family planning and HIV services in multiple countries in Africa [24,31,32].…”
Section: Resultsmentioning
confidence: 99%
“…While most of the studies considered a lifetime time horizon for the analysis, the studies in HIV-positive women considered a relatively short (1 year) time horizon for their analysis. Despite the fact that many studies applied a lifetime time horizon, only very few mentioned or reported the discount rates for both cost and health outcome [26,29,30]. Detailed information about categories of included costs was provided in Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This has been measured recently in two Pacific nations, Vanuatu and Solomon Islands, where the unmet need for family planning is estimated to be 28–33% and 11–12%, respectively. Estimated effects of the reduced fertility (down to 2.1% in Vanuatu and 3.5% in Solomon Islands) are substantial falls in maternal and infant deaths and substantial net cost savings . Substantial levels of unmet family planning needs are also reported from demographic and health surveys (DHSs) in Samoa (45.6%) and Tuvalu (24.6%)…”
Section: Reducing the Unmet Need For Family Planningmentioning
confidence: 99%